Association between sleep quality and participation in people with spinal cord injury: A preliminary study. (4th May 2023) - Conti, Alessio; Sperlinga, Riccardo; Luciani, Michela; Crenna, Maria Francesca; Piovan, Chiara; Scavino, Enrica; Campagna, Sara
Abstract : Objective: To explore the association between perceived sleep quality and participation in people with spinal cord injury (SCI). Design: Cross-sectional study. Setting: Spinal unit at the Città della Salute e della Scienza University Hospital of Turin, Italy. Participants: From May to July 2019, 55 consecutive outpatients were recruited. Outcome measures: A set of structured questionnaires was administered. It included sociodemographic data, the Pittsburgh Sleep Quality Index, the Utrecht Scale for Evaluation of Rehabilitation-Participation, the Spinal Cord Independence Measure Self-Report, the Short Form version 12.2, and the Hospital Anxiety and Depression Scale. T-tests were used to highlight differences between participation and participant characteristics. Bivariate analyses and linear regressions were performed to identify associations between sleep quality and participation. Results: Differences in participation occurred mainly in individuals with a higher level of injury, caregiver dependency, and lower functional level. Participants reporting better sleep quality had more frequent ( r = –0.36, P < 0.01), less restricted ( r = –0.32, P < 0.05), and more satisfactory participation ( r = –0.33, P < 0.01). Linear regression analyses showed that poor sleep quality was significantly associated with reduced participation frequency ( β = –0.30, P = 0.03) and less satisfaction with participation ( β = –0.49, P < 0.001). Moreover, age, number of hours slept at night, and time since injury were associated with satisfaction with participation. Conclusions: An association was found between sleep quality and participation in people with SCI. Given the high prevalence of sleep problems and their association with all dimensions of participation, the promotion of sleep quality should be encouraged because it may positively affect participation.